2017
DOI: 10.5433/1679-0359.2017v38n4supl1p2479
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic structure of mangabeira (Hancornia speciosa Gomes), a fruit species from Cerrado

Abstract: Hancornia speciosa Gomes, popularly known as mangabeira, is a fruit tree belonging to the Apocynaceae family, native to the Brazilian Cerrado. The fruit is widely used by the local population as an alternative source of income. Limited information is available about this species, which increases the difficulty of conserving its genetic resources and exploiting mangabeira as an economic resource. The objective of this research was to evaluate the genetic diversity and genetic structure of H. speciosa from Chapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
6
0
1
Order By: Relevance
“…Research on the mangaba tree is recent, especially the studies of genetic diversity using different molecular markers, such as RAPD [1] [2], ISSR [6] [7] [8] [9] and SSR [10]. These studies are important to assist in the knowledge of the genetic diversity of native populations and accessions, and can be used as tools to design conservation strategies and collection of new accessions to be introduced into the germplasm bank.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the mangaba tree is recent, especially the studies of genetic diversity using different molecular markers, such as RAPD [1] [2], ISSR [6] [7] [8] [9] and SSR [10]. These studies are important to assist in the knowledge of the genetic diversity of native populations and accessions, and can be used as tools to design conservation strategies and collection of new accessions to be introduced into the germplasm bank.…”
Section: Introductionmentioning
confidence: 99%
“…Higher values of Nei (He) and Shannon Index (I) genetic diversity were found in the population of Baixa Grande (He = 0.36 and I = 0.53). This population also presents higher values of observed alleles (na -1.96) and effective alleles (ne -1.61), showing less effect of genetic drift (Soares et al, 2017). However, actions that can reduce the number of individuals in the population could contribute to their isolation and genetic drift.…”
Section: Resultsmentioning
confidence: 82%
“…In genetic diversity studies carried out with H. speciosa, the variation of the heterozygosity index in populations has been reported in the state of Pernambuco (Jimenez et al, 2015), Rio Grande do Norte (Costa et al, 2015), Mato Grosso (Soares et al, 2017), Sergipe (Silva et al, 2017) and Goiás (Rodrigues et al, 2015). Therefore, maintaining this diversity is a determining factor for the conservation and sustainability of fruit production, of which traditional communities, such as Catchers of Mangaba, have part of their income.…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism verified in this study was inferior to that obtained by Soares et al (2016), using SIRS in natural mangaba populations in the State of Sergipe, and observed loci with 100% polymorphism. Soares et al (2017) and Costa et al (2015) in a study of genetic diversity of mangabeiras obtained percentages of polymorphisms of 57.89 and 47.62%, respectively Accession BGMangaba/CP genetic structure, estimated by H e (0.42) and I (0.28) values, revealed that genetic variability exists between mangabeira genotypes (Table 3). Heterozygosity (H e ) and the Shannon Index (I) indicated low diversity, which can be explained by the same genotypes having been evaluated in the accession sample.…”
Section: Caracterização Molecularmentioning
confidence: 98%
“…O polimorfismo verificado nesta pesquisa foi inferior ao obtido por Soares et al (2016), utilizando ISSR em populações naturais de mangaba no estado de Sergipe, e observaram locos com 100% de polimorfismo. Soares et al (2017) e Costa et al (2015) em estudo de diversidade genética de mangabeiras obtiveram porcentagens de polimorfismos de 57,89 e 47,62%, respectivamente A estrutura genética do acesso, estimada pelos valores de H e (0,42) e I (0,28), revelaram que existe variabilidade genética entre os genótipos (Tabela 3). A heterozigosidade (H e ) e o Índice de Shannon (I) indicaram baixa diversidade, que pode ser explicada por terem sido avaliados genótipos de um mesmo acesso.…”
Section: Caracterização Molecularunclassified